Safety of catheter-directed thrombolysis for the treatment of acute lower extremity deep vein thrombosis: A systematic review and meta-analysis. Issue 35 (September 2017) - Wang, Li; Zhang, Chuanlin; Mu, Shaoyu; Yeh, Chao Hsing; Chen, Liqun; Zhang, Zeju; Wang, Xueqin
Abstract: Background: Despite established guidelines, catheter-directed thrombolysis (CDT) for the management of acute lower extremity deep vein thrombosis (DVT) should not be overstated because the risks of CDT are uncertain. We performed a meta-analysis to comprehensively and quantitatively evaluate the safety of CDT for patients with acute lower extremity DVT. Methods: Relevant databases, including PubMed, Embase, Cochrane, Ovid MEDLINE, and Scopus, were searched up to January 2017. The inclusion criteria were applied to select patients with acute lower extremity DVT treated by CDT or compared CDT with anticoagulation. In case series studies, the pooled estimates of safety outcomes for complications, pulmonary embolism (PE), and mortality were calculated across studies. In studies comparing CDT with anticoagulation, summary odds ratios (ORs) were calculated. Results: Of the 1696 citations identified, 24 studies (6 comparing CDT with anticoagulation and 18 case series) including 9157 patients met the eligibility criteria. In the case series studies, the pooled risks of major, minor, and total complications were 0.03 (95% confidence interval [CI]: 0.02–0.04), 0.07 (95% CI: 0.05–0.08), and 0.09 (95% CI: 0.08–0.11), respectively; other pooled risk results were 0.00 for PE (95% CI: 0.00–0.01) and 0.07 for mortality (95% CI: 0.03–0.11). Our meta-analysis of 6 studies comparing the risk of complications and PE related to CDT with those related to anticoagulation showed that CDT was associated with an increased risk of complications (OR = 4.36; 95% CI: 2.94–6.47) and PE (OR = 1.57; 95% CI: 1.37–1.79). Conclusion: Acute lower extremity DVT patients receiving CDT are associated with a low risk of complications. However, compared with anticoagulation, CDT is associated with a higher risk of complications and PE. Rare mortality related to thrombolytic therapy was reported. More evidence should be accumulated to prove the safety of CDT.